Titania-coated silica nanocomposite for L-band noise-like pulse fiber laser - Mohd Yusoff, Norita; Lee, Han Kee; Ng, Eng Khoon; Rosli, Natrah Shafiqah; Che Abdullah, Che Azurahanim; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (Elsevier, 2023)
A nanocomposite of titania-coated silica saturable absorber (TiO2–SiO2-SA) was fabricated via alkaline fusion and spin-coating. The TiO2–SiO2-SA possessed nonlinear saturable absorption and optical limiting effect with 30.35% modulation depth, 42.57 μJ/cm2 saturation fluence, and 0.0075 cm2/μJ two-photon absorption coefficient. By designing a ring cavity erbium-doped fiber laser in net normal dispersion regime and TiO2–SiO2-SA as mode-locker, a stable noise-like pulse (NLP) at 1.57 μm with ∼21 nm spectral bandwidth was initiated at low threshold power of 22.6 mW, and maintained its operation at maximum pump power of 234 mW. A pulse spike of 587 fs riding on 4.47 ps pulse pedestal at 7.66 MHz repetition frequency confirmed its NLP regime. The generated NLP with TiO2–SiO2-SA was very stable and estimated damage threshold of at least 786 μJ/cm2 pumping fluence suggest its potential as one of next generation nanocomposite materials for ultrafast photonics.